Build and Design of Voyage Account Applications Using C#, WPF, and SQL Server 2012 (Case Study Company X) - Sulistyarini, Desi Dyah; Isman, Reza Kamaluddin; Maulana, Hata (Pusat Penelitian Informatika - LIPI, 2017)
Voyage Account is an application that record consumption data on each voyage, then the data is used to calculate the profit or loss of each voyage. The application interface was created using Windows Presentation Foundation (WPF). Prototyping development methods were used to create these applications, C# as the programming language, and SQL Server 2012 as the database. This study discusses the making of the interface, backend, and database of application. WPF has been selected, because WPF is the latest technology developed by Microsoft after WinForms. WPF presents a display that can be customized to user needs. The test results showed that the Voyage Account application is already functioning in accordance with wishes of the user, the test is done using sql query by entering the appropriate username and password and match the query returns results with what is displayed by the application. As for testing the interface shows if WPF can be flexibly adapted to the screen resolution of 1366 x 768, 1920 x 1080 and 1280 x 720.Keyword:Â Voyage Account, WPF, prototyping, C#, SQL Server 2012.